KEDUDUKAN HUKUM BAGI ANAK DARI HASIL PERKAWINAN KONTRAK - Sinulingga Risna Sharon (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT            Marriage is felt as a sacred and special momentum, because generally marriage is only once in a lifetime. This means that marriage is eternal without knowing the time limit. No wonder that most people throw a magnificent party for their marriage processions, even willing to spend quite expensive for the procession that only takes place in a matter of hours. Seeing this reality, marriage is considered a very important and historic thing in the development phase of human life.            Throughout the history of the formulation of the Marriage Law in Indonesia, it always involved three interests / parties, namely the interests of religion, the state and women. In connection with a child's problem, usually in a contract marriage it is avoided to have children. In contract marriages all the legal consequences described above are difficult to implement. This is because the marriage itself is not legal, so it has no legal consequences for both parties. In this case the disadvantaged is women. Women who have gone through contract marriages still have needs that must be met after the contract marriage ends.            The legal reason behind the rechtsvinding is to emphasize that even children outside of marriage are entitled to legal protection. The constitutional judges have legal considerations that encourage the necessity of providing fair legal protection and certainty to the status of a child born and the rights that exist to him, including to children born even though the validity of his marriage is still disputed. Formulation of the problems that arise from the background above among others: (1) Is contract marriage known in Marriage Law Number 1 of 1974? (2) What is the effect of the law of contract marriage on the position of the child after the termination of the contract marriage?            So it can be concluded: (1) The concept of contract marriage is not known in Marriage Law Number 1 of 1974. This is implied from the contents of the articles contained in it, so that it can be concluded on all aspects determined in Law No. 1 year. 1974 married a contract unknown. In contract marriages the nature of marriages is only temporary, making it not in line with the objectives of a marriage according to the marriage law, other than that it does not record marriages that are made with the existing system of contract marriages. marriage law, the marriage is registered in order to have legal force. (2) The legal consequences of contract marriages on the position of the wife is that the wife must carry out all obligations as a wife in general. The position of the wife who does not have a marriage certificate causes the wife does not have any legal power to demand fulfillment of the obligations of her contracted husband, to protect herself as well as both her physical and spiritual needs. Clearly, the legal protection for women is still very weak. Keywords: Contract Marriage, Child Status